Let farmers judge : experiences in assessing the sustainability of agriculture - Hiemstra, Wim.; Reijntjes, Coen.; Werf, E. J. van der. (London, U.K. : Intermediate Technology Publications, 1992)
Contributed articles.
Includes bibliographical references (p. [205]).
Keywords: Sustainable agriculture; Sustainable agriculture -- India; Agriculture -- Economic aspects -- India